DISTRIBUTION OF SPIDERS OF KANYAKUMAR WITH SPECIAL REFERENCE TO HETEROPODA VENATORIA, ARGIOPE PULCHELLA AND STEGODYPHUS SARASINORUM - SUNITHA, S.; MIRANDA, M.T.P. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2011)
Distribution of selected species of spiders Heteropoda venatoria, Argiope pulchella and Stegodyphus Sarasinorum of Kanyakumari district was studied for a period of one year from September 2005 to August 2006. Intensive field work was undertaken regularly and spiders were observed and collected every week at Kuzhithurai ( 8°19' N Latitude 77° 1' E Longitude), Kolachel (8° 10' N. Latitude 77° 14' E Longitude) and Kanyakumari (8°4' 60 N Latitude 77°34' E Longitude) in Kanyakumari district. The spiders were collected from a wide variety of manmade structures, fields and forests and locality records were kept. Analysis of morphometry include the colour and position of the eye, the total length, length of cephalothorax, abdomen, I, II, III and IV legs were recorded.